Estudio para industrializar el proceso de fabricación de fuegos pirotécnicos en el taller artesanal, pirotecnia Santo Domingo, del cantón Santo Domingo, año 2014 - Pantoja Patiño, Oscar Rafael (2015)
Pyrotechnics company in Santo Domingo located in the canton of the same name, a study was conducted to industrialize the process of making fireworks, in order to improve productivity and profitability. To meet the objectives a diagnosis of the current situation, using techniques of descriptive and explanatory literature search was performed. The research methodology of the subject of study was based on statistical methods, deductive, analytical, descriptive and quantitative; to determine the sample size we proceeded to segment the population, given that the use of pyrotechnics is aimed at a cluster of people grouped especially in: districts, communes, precincts and townships, it was found that the total population of this segment amounted a number of 954 persons for purposes of research surveys were conducted by sampling to 274 people with a confidence level of 95% and an error of 5%. These surveys reveal that there is unmet demand it can be covered by the company Santo Pyrotechnics Sunday when they industrialize their processes. The application of investigative tools make the best decisions possible to identify and select the right kind of machinery that can be used in the industrial process for the production of fireworks. The initial investment which will allow industrialization to an amount of $ 89.963,14 them to be financed entirely by the shareholders of the company. The results of the financial analysis result of a projected cash flow for five years indicate that the internal rate of return (IRR) is 63% and the net present value (NPV) is $ 94.504 these two indicators are excellent and attractive to the shareholders of the company in the benefit-cost ratio is projected that they will receive $ 1,81 profit for every dollar invested.